ISOLATION AND SELECTION OF INDIGENOUS ANTIFUNGAL MICROORGANISMS AGAINST PATHOGENIC FUNGI OF PEPPER PLANT IN TAY NGUYEN - Thuy Hoai, Pham Thi; Huu Dat, Ton That; Hong, Tran Thi; Kim Cuc, Nguyen Thi; Man, Tran Dinh; Cuong, Pham Viet (Vietnam Journal of Biotechnology, 2018)
The pathogenic fungi often cause huge impacts on agricultural crops, and occupy over 80% of plant diseases. Fusarium oxysporum and Rhizoctonia solani are fungal pathogens that can lead to rapid development of plant diseases on important crops in Tay Nguyen (e.g., pepper, coffee, rubber, cashew). Therefore, the study of microorganisms with bioactivity against these pathogens is essential to control plant diseases. In this study, we isolated microorganisms from rhizospheres of pepper in Tay Nguyen and screened beneficial microbes against two pathogenic fungi using agar well diffusion assay. Obtained results showed that there are different about isolated microbial density between samples collected from diseased and healthy pepper. The bacterial population is higher in rhizosphere region of healthy pepper than in those of diseased plants. In contrast, fungal density is lower in rhizosphere region of healthy plants than in those of diseased ones. From isolation plates, we selected and purified 391 strains including 236 bacteria, 149 actinomycetes and 6 fungi for screening antifungal activity. Out of isolated microorganisms, 44 strains (36 bacteria, 6 actinomycetes, and 2 fungi) showed antagonistic activity against at least one of two pathogens (F. oxysporum and R. solani), of which 15 isolates showed activity against both fungi. Identification of isolates with highest activity using the 16S rRNA gene sequences showed bacterial strains belonged to different species Enterobacter ludwigii, Pseudomonas fulva, Bacillus subtilis, whereas 2 actinomycetes belonged to the genus Streptomyces: Streptomyces sp. and Streptomyces diastatochromogenes. Identification of the isolated fungus based on morphological characteristics and the 18S rRNA gene sequence revealed that this strain belonged to species Penicillium oxalicum. Our study revealed the potential of the indigenous microorganisms in preventing and controlling plant-pathogenic fungi.